CRIS systems in practice: Some workflows around open access, research data management and reporting - de Castro, Pablo (2018)
University of Strathclyde in Glasgow: Established 1796 as “the place for useful learning", 21,470 FTE Students and 3,200 staff, research: research grants and contracts income of £59,921m in 2016, Among the 20 top research-intensive universities in the UK. Previously: OpenAIRE2020 WP coordinator at LIBER (Assoc of European Research Libraries) in The Hague, the Netherlands, EDINA National Data Centre, University of Edinburgh, UK, Consejo Superior de Investigaciones Científicas (CSIC), Universidad Carlos III Madrid UC3M), Spain